2012
DOI: 10.1152/ajprenal.00248.2012
|View full text |Cite
|
Sign up to set email alerts
|

Forskolin stimulation promotes urea transporter UT-A1 ubiquitination, endocytosis, and degradation in MDCK cells

Abstract: The adenylyl cyclase stimulator forskolin (FSK) stimulates UT-A1 phosphorylation, membrane trafficking, and urea transport activity. Here, we found that FSK stimulation induces UT-A1 ubiquitination in UT-A1 Madin-Darby canine kidney (MDCK) cells. This suggests that phosphorylation by FSK also triggers the protein degradation machinery for UT-A1. UT-A1-MDCK cells were treated with 100 μg/ml cycloheximide to inhibit protein synthesis, with or without 10 μM FSK. Total UT-A1 protein abundance was significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Cell surface protein expression was evaluated using the membrane-impermeable biotinylation reagent NHS-SS-biotin, as previously described [21]. Briefly, cells were seeded on 6-well plates and cultured with 1.2 ml of NHS-SS-biotin (0.6 mg/ml in a borate buffer) in two successive 20-min incubations on ice with very gentle shaking.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell surface protein expression was evaluated using the membrane-impermeable biotinylation reagent NHS-SS-biotin, as previously described [21]. Briefly, cells were seeded on 6-well plates and cultured with 1.2 ml of NHS-SS-biotin (0.6 mg/ml in a borate buffer) in two successive 20-min incubations on ice with very gentle shaking.…”
Section: Methodsmentioning
confidence: 99%
“…EGFR internalization was measured via biotinylation and sodium 2-mercaptoethane sulfonate (MesNa) treatment [21]. In short, the membranous proteins on the cell surface were first biotin-labeled with a freshly prepared solution of 0.6 mg/ml EZ-Link sulfo-NHS-SS-biotin (Pierce 21331) in a borate buffer as described above.…”
Section: Methodsmentioning
confidence: 99%
“…The pcDNA3 FLAG-Tac-UT-A1, an external FLAGtagged UT-A1, has been described before (29). Amino acids of serine at 486 and 499 of UT-A1 PKA sites were mutated to alanine by site-directed mutagenesis.…”
Section: Methodsmentioning
confidence: 99%
“…We recently found that FSK, the adenylyl cyclase stimulator often being used for in vitro experiments to stimulate UT-A1 urea transport activity, can promote UT-A1 ubiquitination and protein degradation, revealing the coin's other side of UT-A1 phosphorylation by vasopressin or FSK (29). This suggests that activation of the cAMP/PKA pathway causing UT-A1 phosphorylation also triggers the protein ubiquitination and degradation machinery for UT-A1.…”
mentioning
confidence: 99%
“…We recently reported that FSK, the adenylyl cyclase stimulator often used for in vitro experiments to stimulate UT-A1 urea transport activity, can also promote UT-A1 ubiquitination and protein degradation, revealing the other side of UT-A1 phosphorylation by vasopressin or FSK (29,30). This observation has led to the hypothesis that phosphorylation could be required for UT-A1 ubiquitination.…”
Section: F76mentioning
confidence: 99%